PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI AUDITOR, TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Pandji Pratama, (2022)
This study was conducted to practically test the effect of professional skepticism, auditor independence, time pressure on the auditor's ability to detect fraud. The population of this study includes all auditors at the South Jakarta Public Accounting Firm registered at the OJK in 2020 using a purposive sampling technique. This research is a quantitative type with primary data in the form of a questionnaire and processed using SPSS version 26. The results of this study, namely Professional Skepticism and Time Pressure have an effect on the Auditor's Ability to Detect Fraud, but Auditor Independence has no effect on the Auditor's Ability to Detect Fraud.